The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1515/cclm.1982.20.3.119
|View full text |Cite
|
Sign up to set email alerts
|

On the Effects of Ambilhar on Mobilisation and Biliary Excretion of Mercury

Abstract: Summary: The effects of administration of ambilhar to rats poisoned with mercury for two weeks were investigated. The results showed that administration of ambilhar to rats dosed with mercuric Chloride, resulted in a significant increase in the faecal excretion of mercury. At the same time a significant decrease in the urinary Output of the metal was found. Chelation of ambilhar with mercury to form a polar complex with a higher molecular weight could explain its biliary rather than its urinary excretion. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Later, Abdel Aziz et al (5) reported that niridazole stimulated the biliary excretion of mercury in rats. This finding was explained by the formation of a polar complex with mercury of a higher molecular weight, which undergoes biliary rather than urinary excretion.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Abdel Aziz et al (5) reported that niridazole stimulated the biliary excretion of mercury in rats. This finding was explained by the formation of a polar complex with mercury of a higher molecular weight, which undergoes biliary rather than urinary excretion.…”
Section: Introductionmentioning
confidence: 99%